Animation and Audio-Based Illustrated Story Media for Elementary School Students - Restu Resky Satriya; Eni Fariyatul Fahyuni (Journal of Education Technology, 2025)
The issue of prayer learning in elementary schools remains a challenge, as the learning media used are generally static and lack interactivity. This condition causes students’ understanding of prayer procedures and their spiritual essence to remain limited to mechanical aspects without meaningful reflection on the values of worship. This study aims to develop and examine the effectiveness of an interactive Islamic picture story-based learning media integrated with animation and audio to enhance students’ understanding of prayer. The research employed a development approach using the ADDIE model combined with a quasi-experimental design. The study involved material experts, media experts, learning experts, and lower-grade elementary students as participants. Data were collected through observation, questionnaires, and tests using validation sheets, practicality questionnaires, and comprehension tests. The data were analyzed using descriptive qualitative, quantitative, and inferential statistical techniques. The results indicate that the developed media are valid, practical, and effective in improving students’ understanding of prayer compared to conventional learning. It can be concluded that the animation- and audio-based learning media enhance students’ understanding of both the procedures and spiritual values of prayer. The study implies that interactive media can serve as an engaging, meaningful, and contextual alternative for Islamic education learning